IMPACT OF EMPLOYEE WELFARE FACILITIES ON JOB SATISFACTION WITH SPECIAL REFERENCE TO CHENNAICITY - Ms. G.Anitha , Dr.R.Sridharan, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Employee Welfare is words includes variety of service, reimbursement along with services obtainable toward the employees through the employer. During like liberal edging reimbursement the manager make time value income used for worker. The essentialuse of member of staff benefit be toward enhance the living of workers with stay them joyful as well as happy. Employee welfare procedures inspire the workers meant for the improved presentation, moreover boost awake employee self-esteem with improve the human being connection plus it increase the job satisfaction of the workers. Job satisfaction is a versatile conception. It is important element of managerial atmosphere as well as it be significant part into the organization of worker affiliation. Consequently the research objectiveis to study the impact of employee welfare measures on job satisfaction